Charms for the easy life - Gibbons, Kaye (New York : G. P. Putnam's Sons, 1993)
A family without men, the Birches live gloriously offbeat lives in the lush, green backwoods of North Carolina. Radiant, headstrong Sophia and her shy, brilliant daughter, Margaret, possess powerful charms to ward off loneliness, despair, and the human misery that often beats a path to their door. And they are protected by the eccentric wisdom and muscular love of the remarkable matriarch Charlie Kate, a solid, uncompromising, self-taught healer who treats everything from boils to broken bones to broken hearts.
Keywords: Women healers -- Fiction; Domestic fiction